A Proposal Of OEE Simulation Decision Support Tools For Lean Practitioners - Mohd Yunos, Ahmad Syafiq (2016)
Nowadays, Lean Manufacturing (LM) is a driving method for companies in order to succeed in global competition. Reducing as well as eliminating waste in production line using equipment is the main use of LM innovations. Having an expert in LM is a good way for companies to balance and maintain in order to deliver a good value to the customers. Nevertheless, some aspects are hard for the LM practitioner to evaluate the impact of LM tools at certain desired level after deciding and implementing appropriate LM. Hence, may negatively affect the resources and time consumed as well as cost. The aim of this study is to suggest a simulation framework of LM tools for LM practitioners which are Overall Equipment Effectiveness (OEE) in simulation-based decision support tools (SDST). The architecture of OEE-SDST based on the original framework of OEE concepts by Nakajima (1988). Integrating the average cost by relating OEE efficiency is a one of the new introductions in OEE concepts. The design and development will be built on the Microsoft Visual Basic 2010. The OEE-SDST will operate as graphical user interface(GUI). The usability study of software capability criteria based on ISO/IEC 25010:2011 or ISO/IEC 9126 that consist of understandability, learnability, operability, and attractiveness. Based on the 50 respondents, about 78% are agreed with capabilities of the OEE-SDST. To conclude, OEE-SDST capable of assist the decision making for the LM practitioner.